Teologi Doa Yohanes Calvin sebagai Kritik terhadap Mistisisme dan Pragmatisme Iman dalam GMIM - Sella Paningidang; Riedel Ch Gosal (STT INDONESIA MANADO, 2026)
Abstract: Contemporary church life demonstrates a tendency to view prayer from both mystical and practical perspectives. Prayer is often viewed as a means to gain benefits, supernatural powers, and a measure of the success of one's faith. This has even led to the creation of cults of worship for those deemed to have